REPRESENTING RAPE – LANGUAGE AND SEXUAL CONSENT - Van Zyl, Gerhard (Scientia Militaria - South African Journal of Military Studies, 2012)
Ehrlich cuts right through and beyond linguistic jargon to reach to the bone and marrow of both scientific and ordinary users of language by revealing how language is used by those in power to keep them in power. Is there a need for such acute surgery in a South African context, and in particular in an SANDF context?